Great world religions Judaism - Gafni, Isaiah M. (Great courses : Religion, 2003)
Surveys the history, traditions, and practice of Judaism from biblical times to today, with explanations of the major aspects of Jewish culture. Focuses on Judaism from within and how it is understood by its adherents, past and present. Covers topics such as the sacred books of Judaism, modes of worship, the calendar and holidays, and rites of passage such as bar and bat mitzva and marriage. Illustrates how Judaism reinvented itself by embracing the rabbinical tradition after the destruction of the Second Temple in 70 C.E. and considers the thinking of philosophers such as Maimonides.